PENSION VALORIZATION METHOD – SELECTED ISSUES - Kobylińska, Anna; Balcerowski, Maciej (Copernican Journal of Finance & Accounting, 2018)
The aim of this article is to present basic terms and issues connected with pension valorization. Within the framework of this paper were presented methods of valorization and development of valorization in time. Particular attention has been paid to the issue of jurisdiction of the Polish Constitutional Tribunal K 9/12 mentioned fixed valorization from 2012. Historical analyze is a measure to determine minimal standards of valorization according to Polish Constitution.